Relationship of Emotional Intelligence with Learning Outcome of Students in SMP Negeri 13 Padang - Yanti Oktavia; Netrawati Netrawati (Universitas Negeri Padang, 2019)
Learning is process of effort by someone to get a new level of behavior change as a whole, as a result of their own friendship with the environment. Students will obtai their outcome of their studied where students must go trough the learning process their follows. Learning outcomes is a effect they get after applying their lessons, each learning process is usually measured by the success of learning outcomes. The success of a student in participating in learning can be seen from the learning outcomes obtained.besides the factors that cause aperson to be successful in learning is to have emotional intelligence. Emotional intelligence will able to train and manage feeling in motivating themself, the ability to control impulse for a moment, empathize, the ability to be strong in dealing with frustration, working with others, and the mood. This study aims to determine the relation of emotional intelligence with student learning outcomes in SMP N 13 Padang.This research includes quantitative research with cholerational approach. The population of this study is the student of class VIII and X SMP N 13 Padang which amounts to 529 people. The sampling done by technique proportional random sampling. The sample from this study amounted 233 people. This research was conducted by administering the research questionnaire instrument. Data analysis with correlational statistical techniques.Research findings show 1) In general students have emotional intelligence in recognizing their emotions are in the medium category 2) In general students have emotional intelligence in the aspect of managing emotions in the medium category 3) In general students have emotional intelligence in the aspect of recognizing self motivation are in the medium category 4) In general students have emotional intelligence in terms of recognizing the emotions of others in the medium category 5) In general students have emotional intelligence in aspects of a good relationship with others in the medium category 6) In general students have learning outcomes in the low category. Based on the research findings it can be concluded that the students of SMP N 13 Padang are in the medium category in an emotional relationship with learning outcomes.